2020
DOI: 10.1097/ccm.0000000000004378
|View full text |Cite
|
Sign up to set email alerts
|

Financial Toxicity After Acute Respiratory Distress Syndrome: A National Qualitative Cohort Study*

Abstract: Objective: The financial burdens and subsequent related distress of medical care, referred to as financial toxicity, may limit access to beneficial treatments. However, financial toxicity after acute care is less described-but may be an important but underexplored mechanism preventing full recovery after critical illnesses such as Acute Respiratory Distress Syndrome (ARDS). We sought to identify the mechanisms by which financial toxicity manifested in patients with ARDS, protective factors against such toxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 31 publications
3
41
0
Order By: Relevance
“…Forty-six patients agreed to participate in interviews, of which 67% reported some form of negative financial impact they attributed to their ARDS hospitalization. Although this is a small study, the authors found, at a very granular level, that patients who acquired medical expenses as a result of their ARDS hospitalization experienced financial toxicity that outweighed their available resources ( 7 ). Some patients described their financial toxicity as limiting their recovery by causing adverse mental health effects and altering their medication or rehabilitation compliance due to an inability to pay.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Forty-six patients agreed to participate in interviews, of which 67% reported some form of negative financial impact they attributed to their ARDS hospitalization. Although this is a small study, the authors found, at a very granular level, that patients who acquired medical expenses as a result of their ARDS hospitalization experienced financial toxicity that outweighed their available resources ( 7 ). Some patients described their financial toxicity as limiting their recovery by causing adverse mental health effects and altering their medication or rehabilitation compliance due to an inability to pay.…”
mentioning
confidence: 99%
“…Although the macro estimates for these healthcare costs are substantial, they fail to account for the human and financial impact on individual patients and families at the micro level. In this issue of Critical Care Medicine , the article by Hauschildt et al ( 7 ) provides a rare opportunity to give audience to the micro level financial experience after an ICU stay from the patient’s perspective and how the consequential costs either burdened or buffered the patient’s recovery ( 7 ).…”
mentioning
confidence: 99%
See 3 more Smart Citations